IMPLEMENTATION OF SCHOOL CULTURE TO STRENGTHEN STUDENT CHARACTER AT MADRASAH IBTIDAIYAH KHADIJAH IN MALANG CITY - Maulidin, Ahmad; Mesgiyanto, Chairul Bahri; Suhartono, Suhartono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to describe the implementation of school culture to strengthen the character of students at Madrasah Ibtidaiyah Khadijah in Malang City, the inhibiting factors, and the efforts made. The method used in this research is qualitative research. Data collection was carried out using observation, interviews, and documentation techniques. Data analysis was conducted using the Miles and Huberman model analysis technique. In this study, the research subjects were the principal, teachers, and students at Madrasah Ibtidaiyah Khadijah in Malang City. The results of the study indicate that religious character is implemented through regular and spontaneous practices, such as performing Dhuha prayers every day, reciting prayers before and after studying, practicing ablution, memorizing short surahs, and daily prayers. The character of independence is implemented through regular, spontaneous habits, and role modeling. The character of discipline is implemented through regular, spontaneous habits, and role modeling. The obstacles encountered include parents who have personal busy schedules, inadequate facilities and infrastructure, and an unsupportive environment. The solutions provided are to conduct socialization with parents and emphasize the importance of character education applied at home as well as building a special closeness with students